Safety evaluation of the food enzyme α‐amylase from the genetically modified Bacillus licheniformis strain DP‐Dzb106 - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize Solano; Henk Van Loveren; et al. (EFSA Journal, 2025)
Abstract The food enzyme α‐amylase (4‐α‐d‐glucan glucanohydrolase; EC 3.2.1.1) is produced with the genetically modified Bacillus licheniformis strain DP‐Dzb106 by Genencor International B.V. The production strain met the requirements for the qualified presumption of safety (QPS). The food enzyme was considered free from viable cells of the production organism, but not from its DNA. It is intended to be used in three food manufacturing processes. Since residual amounts of food enzyme–total organic solids (TOS) are removed in two food manufacturing processes, dietary exposure was calculated only for the remaining one. It was estimated to be up to 2.084 mg TOS/kg body weight per day in European populations. Given the QPS status of the production strain and the absence of concerns resulting from the food enzyme manufacturing process, the Panel considers toxicity tests unnecessary. A search for the homology of the amino acid sequence of the α‐amylase to known allergens was made and no match was found. The Panel considered that a risk of allergic reactions upon dietary exposure to the food enzyme cannot be excluded, but that the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns, under the intended conditions of use.